HUBUNGAN TERPAAN PESAN PERINGATAN BAHAYA MEROKOK DAN TINGKAT PENGETAHUAN TENTANG ROKOK DENGAN MINAT BERHENTI MEROKOK PADA REMAJA - Bella Prawilia; Sri Widowati Herieningsih; Tandiyo Pradekso; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2015)
The number of teenage smokers in Indonesia has increased each year. Government's efforts in reducing the number of smokers is to include a warning message about the dangers of smoking on cigarette advertisements. The latest warning message has a difference with the previous warning message. The latest one are have picture and with a shorter sentence.This research is a quantitative study with explanatory type, which aims to knowing correlation between exposure to warning message about the dangers of smoking and level of knowledge about cigarette to interest in quitting smoking in adolescents. The theory used is the theory of Cognitive Response. The population of the research was teenage boys who become an active smokers with population numbers unknown. This research uses technique of non-random sampling which taken samples 60 people. The primary data were analyzed using Pearson correlation test with the help of SPPS program.The results of the Pearson correlation analysis show that between variable exposure to warning message about the dangers of smoking (X) with variable level of knowledge about smoking (Z) has a significant correlation. This is shown by the value of significance is 0,033 which mean the level of significance is smaller than 0.05 and the value of the correlation coefficient is 0,276. Variable level of knowledge about smoking variables (Z) with variable interest in quitting smoking (Y) has significant correlation. This is showed by the value of significance is 0.005 which mean smaller than 0.05 and the value of the correlation coefficient is 0,359.The government as policy maker about warning message on cigarette advertisements should be consistent in an effort to reduce the number of smokers in Indonesia. The proportion of warning message can be wider in print media and outdoor media and also give more duration on cigarette advertisements in electronic media so it can be more clearly seen by all audiences.Key words: Exposure to Warning Message, Level of Knowledge, Interest in Quitting Smoking.